Relationship between self-esteem and academic progress in physiotherapy students at Babol University of Medical Sciences - Arsalan Ghourbanpour; Ghadamali Talebi; Mohammad Taghipour (Babol University of Medical Sciences, 2016)
ABSTRACT BACKGROUND AND OBJECTIVE: Indentifying the factors affecting on educational progress and or academic degradation is very impotent in education fields. Some researchers have been reported a direct relation between the self-esteem and educational progress, while another authors have doubted such direct relation. This study was aimed to determining the relationship between self-esteem and educational progress in physiotherapy students at Babol University of medical sciences. METHODS: In this correlation study, initially 52 physiotherapy students, undergraduate level, interred; but finally 45 subjects completed the questionnaire with the consent and consciously. The questionnaire included two parts: demographic information's and cooper-smith valid test with 58 questions. The cooper-smith questionnair was used to measuring the student's self-esteem. Also, the correlation between self-esteem and average score and other demographic data was surveyed. Data analyzed using pearson's test and t-test via SPSS. FINDINGS: The mean of student's self-esteem and their average score determined 34.10±6.34 and 16.866±1.059 respectively. There was not a significant correlation between the student's self-esteem and average score (p=0.255). The mean of student's self-esteem was significantly lower in boy students (32.00±5.394) with respect to girl students (36.42±6.628) (p=0.028). A significant correlation was found between student's self-esteem and marital status (p=0.020); the mean of self-esteem in married students and unmarried students were 41.00±1.414 and 33.33±6.211. Additionally, there was not found any significant correlation between Paternal education level and student's iterance rank and between age and self-esteem (p>0.05). CONCLUSION: The student's self-esteem is a Complex issue and somewhat independent of educational progress and Paternal education level. Interestingly, self-esteem was higher in girl's students and married individuals with respect to boy's students and unmarried individuals respectively.